2016
DOI: 10.1007/s00467-016-3428-z
|View full text |Cite
|
Sign up to set email alerts
|

A dedicated vascular access clinic for children on haemodialysis: Two years’ experience

Abstract: BackgroundArteriovenous fistula (AVF) formation for long-term haemodialysis in children is a niche discipline with little data for guidance. We developed a dedicated Vascular Access Clinic that is run jointly by a transplant surgeon, paediatric nephrologist, dialysis nurse and a clinical vascular scientist specialised in vascular sonography for the assessment and surveillance of AVFs. We report the experience and 2-year outcomes of this clinic.MethodsTwelve new AVFs were formed and 11 existing AVFs were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The observed high proportion of CVC as first vascular access (56%) in European practice is in contrast to recommendations in recent initiatives and guidelines, but in keeping with previous studies [10, 15, 16]. Some large US studies even reported a CVC usage of 80–90% in incident HD children [10, 17, 18].…”
Section: Discussionsupporting
confidence: 81%
“…The observed high proportion of CVC as first vascular access (56%) in European practice is in contrast to recommendations in recent initiatives and guidelines, but in keeping with previous studies [10, 15, 16]. Some large US studies even reported a CVC usage of 80–90% in incident HD children [10, 17, 18].…”
Section: Discussionsupporting
confidence: 81%
“…According to the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF-KDOQI) guidelines, the ideal vascular access is described as one which can deliver an adequate flow rate along with durability and a low complication rate. An arteriovenous fistula (AVF) is usually considered to be the best access for HD in adults and, as commented on by an emerging body of evidence, that it is the same also in children [12].…”
Section: Arteriovenous Fistula Creationmentioning
confidence: 99%
“…With good play therapy and the use of local anaesthetic creams, fistulae can be successfully used even in very young children [17]. The development of a dedicated clinic with a multidisciplinary team of specialised ultrasonographers, a nephrologist, a senior haemodialysis nurse and a vascular surgeon has encouraged the use of arteriovenous (AV) fistulae and their maintenance after creation [18]. It has to be remembered that every patient has only five lifelines: two arms, two legs and the peritoneum.…”
Section: What Ways Do We Have To Improve the Dialysis Process And Howmentioning
confidence: 99%